Ethanol (EtOH)-Induced TGF-β1 and Reactive Oxygen Species Production Are Necessary for EtOH-Induced Alveolar Macrophage Dysfunction and Induction of Alternative Activation - Brown, Sheena D.; Brown, Lou Ann S. (Alcoholism, clinical and experimental research, 2012)
Background Previous studies have shown that chronic ethanol (EtOH) ingestion results in impaired alveolar macrophage function, increased TGF‐β1 production, and decreased antioxidant availability. Similarly, alternative activation (M2 activation) of alveolar macrophages also induces TGF‐β1 production and impairs macrophage function. However, the potential links between EtOH‐induced alveolar macrophage derangements, M2 activation, TGF‐β1 production signaling, and oxidant stress have yet to be examined. We hypothesized that EtOH‐induced oxidant stress and induction of TGF‐β1 signaling result in alternative activation which subsequently impairs the phagocytic capacity of alveolar macrophages. Methods Primary rat alveolar macrophages and the alveolar macrophages cell line NR8383 were treated with 0.08% EtOH ± the antioxidant glutathione (GSH) or a TGF‐β1 neutralizing antibody for 5 days. Outcome measures included TGF‐β1 production, reactive oxygen species (ROS) production, phagocytic capacity, and expression of markers of M2 activation. Results Chronic EtOH treatment greatly decreased alveolar macrophage phagocytic function, increased ROS production, increased TGF‐β1, and increased expression of markers of M2 activation. GSH supplementation and inhibition of TGF‐β1 signaling during EtOH treatment prevented these alterations. Conclusions EtOH treatment increased oxidant stress, TGF‐β1 production, and alternative activation in NR8383 cells. However, GSH supplementation and ablation of TGF‐β1 signaling prevented these effects. This suggested that the EtOH‐induced switch to an M2 phenotype was a result of decreased antioxidant availability and increased TGF‐β1 signaling. Preventing EtOH‐induced induction of alternative activation may improve alveolar macrophage function in alcoholic subjects and decrease the risk of respiratory infections.